Xiaoshuan enteric-coated capsule alleviates cognitive impairment by enhancing hippocampal glucose metabolism, hemodynamics and neuroplasticity of rat with chronic cerebral hypoperfusion - Man-zhong Li (Nature Portfolio, 2018)
Abstract Chronic cerebral hypoperfusion (CCH) is identified as a critical risk factor of dementia in patients with cerebrovascular disease. Xiaoshuan enteric-coated capsule (XSECC) is a compound Chinese medicine approved by Chinese State Food and Drug Administration for promoting brain remodeling and plasticity after stroke. The present study aimed to explore the potential of XSECC to improve cognitive function after CCH and further investigate the underlying mechanisms. CCH was induced by bilateral common carotid artery occlusion (BCCAO) in rats. XSECC (420 or 140 mg/kg) treatment remarkably reversed BCCAO-induced cognitive deficits. Notably, after XSECC treatment, magnetic resonance angiography combined with arterial spin labeling noninvasively demonstrated significantly improved hippocampal hemodynamics, and 18F-FDG PET/CT showed enhanced hippocampal glucose metabolism. In addition, XSECC treatment markedly alleviated neuropathologies and improved neuroplasticity in the hippocampus. More importantly, XSECC treatment facilitated axonal remodeling by regulating the phosphorylation of axonal growth related proteins including protein kinase B (AKT), glycogen synthase kinase-3β (GSK-3β) and collapsin response mediator protein-2 (CRMP2) in the hippocampus. Taken together, the present study demonstrated the beneficial role of XSECC in alleviating BCCAO-induced cognitive deficits by enhancing hippocampal glucose metabolism, hemodynamics and neuroplasticity, suggesting that XSECC could be a useful strategy in cerebral hypoperfusion state and dementia.